Midnight duet : a novel - Comfort, Jen (Montlake, 2023)
Self-professed diva Erika Greene has it all: a starring role on Broadway, legions of fans, spectacular natural talent. But after an accident on stage leaves her face scarred and her career in shambles, Erika retreats to Paris, Nevada, where she's inherited a ramshackle opera house in desperate need of some TLC. Erika pours her savings into the building, but it's not enough to stave off casino developer Raoul Decomte's avaricious gaze. With foreclosure imminent, she leases the space to some unexpected tenants: a German hair metal band, fronted by glam rock god Christof Daae. Erika is tempted by Christof's low-slung leather pants--and even more so by his ambitious drive to make Nacht Musik international superstars--but he's off-limits. The rest of his band thinks he's still dating their beloved keyboardist, who is conveniently not present on this jaunt to the American Southwest. When Erika finds out Christof's been unceremoniously dumped and is trying to keep it under wraps, she makes a deal to keep his secret...for a price, of course. Christof is desperate to hold the rest of the band together after his keyboardist's departure, but he can't maintain the charade forever. Nor can he resist the opera house's mysterious proprietor, who tempts him with midnight singing lessons. It isn't long before sensuous nighttime interludes turn into smoldering backstage encounters. But can their newly ignited passion survive the searing light of day? Or will their beautiful duet turn into a brokenhearted power ballad for one?